SIaaS - Sensing Instrument as a Service Using Cloud Computing to Turn Physical Instrument into Ubiquitous Service - Di Lauro, R.; Lucarelli, F.; Montella, R. (2012 IEEE 10th International Symposium on Parallel and Distributed Processing with Applications, 2012)
Sensing Instrument as a Service (SIaaS) is a new cloud service that allows users to use data acquisition instruments shared through cloud infrastructure. It offers a common interface to managing physical sensing instrument and it permits to take all advantages of using cloud computing technology in storing and processing acquired data. With SIaaS different research groups could share physical instrument, in a controlled way, event if they are geographically distributed and user can access to them using an internet connected device without the need to install any sort of program. With the interaction of different own framework we have created a new cloud service for transforming physical resources in a ubiquitous service.